Respuesta :
Answer:
sum=17
Step-by-step explanation:
(a+b)*(a-b)=85
let a=11 and b=6
(11+6)*(11-6)=85
85=85
so the two whole numbers are 11 and 6
and, their sum is : 11+6= 17.
Answer:
Step-by-step explanation:
Let the two numbers be denoted by x and y.
1. (x + y) × (x - y) = 85
2. x - y =/= 1
From equation 1,
x^2 - y^2 = 85
x^2 = 85 + y^2
Let y^2 be a perfect square so, the RHS will give a perfect square greater than 85 hence, find x as a perfect square,
y = 6
x^2 = 85 + 36
x = sqrt(121)
= 11
(x + y) × (x - y) = 85
(11 + 6) × (11 - 6)
= 85